Strategi PKBM Nara Kreatif dalam Penanganan Anak Putus Sekolah di Kampung Pemulung Pondok Kopi Jakarta Timur - Zsal Zsal Bila; Martini Martini; Achmad Nur Hidayaht (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The problem of children dropping out of school is still a challenge that must be overcome in realizing equal distribution of education in Indonesia. This is proven in the 2022 Susenas Data on Out of School Children in Indonesia that there are 3,847,780 children who have dropped out of school. This condition is also experienced by the children of the Pondok Kopi Scavenger Village, East Jakarta, as many as 16 scavenger children in the area are unable to continue their education due to lack of funds and cultural conditions that make them stop going to school. PKBM Nara Creative as one of the non-formal education institutions is making efforts to deal with this problem. Therefore, this research aims to find out PKBM Nara Kreatif strategy in dealing with the problem of out-of-school children in Pondok Kopi Scavenger Village, East Jakarta. The research method in this paper is descriptive with a qualitative descriptive approach. By conducting a direct interview with the Project & Partnership Manager of PKBM Nara Kreatif. The results of the research show that in dealing with out-of-school children in Pondok Kopi Pemulung Village, PKBM Nara Kreatif uses an empowerment strategy that is formulated into a program, namely the Trusted Children's School.